Operating Performance of Diverging Diamond Interchanges. Issue 11 (November 2019) - Hunter, Michael; Guin, Angshuman; Anderson, James; Park, Sung Jun
As the result of changing traffic patterns, many conventional intersections and interchanges can no longer accommodate growing traffic volumes and heavy turning movements. In response, there are various innovative intersection and interchange designs proposed and implemented to better accommodate these changes, and the diverging diamond interchange (DDI) is one of these alternatives. While there is a significant amount of research on the relative performance of DDIs and conventional diamond interchanges (CDIs), a clear set of guidance on demand conditions under which a DDI is likely an operationally more efficient solution is not readily available. This effort conducts a sensitivity analysis of CDI and DDI operational performance under various interchange lane configurations, including the selected study area of the Jimmy Carter Boulevard and I-85 interchange in Norcross, Georgia, under varying traffic demands and turn-movement ratios. The sensitivity analysis explores the detailed conditions in which one interchange configuration provides superior performance over the other. The sensitivity analysis is structured into a two-step process with a critical lane volume (CLV) analysis as the first step, followed by a VISSIM microscopic simulation study as the second step. Overall, the study found that a CDI is likely to be the preferred option at locations with traffic volumes well below capacity and cross-street left-turn traffic proportions below 30% of the total cross-street demand, and a DDI is likely to be preferred at locations with traffic volumes near capacity and cross-street left-turn proportions exceeding 50% of the total cross-street demand.